2019
DOI: 10.1021/acs.jafc.9b03099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dielectric Barrier Discharge Cold Plasma on Pea Seed Growth

Abstract: Traditional seed pretreatment methods cause secondary pollution for the application of various chemicals. This study investigated the effect of dielectric barrier discharge (DBD) cold plasma on seedling growth. Effects of plasma-activated tap water (PATW) and plasma-activated seeds (PAS) were compared for germination rates, seedling height, dry weight, and chlorophyll content. Results show that compared with controls these growth parameters were all increased by more than 50%. The yields and contributions of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 49 publications
2
43
1
Order By: Relevance
“…It seems that plasmas may somehow modulate concentrations of hormones and there may be a link with auxin especially considering that this hormone also affects xylem differentiation [173]. It has been observed that plasma treatment modified the diameters of root and stems as well as the differentiation of tissues such as xylem and phloem [51,52,58,174]. These changes in root morphology may then enhance nutrient exchange [68] which was also proposed by Zahoranová et al [97].…”
Section: Hormonesmentioning
confidence: 79%
See 3 more Smart Citations
“…It seems that plasmas may somehow modulate concentrations of hormones and there may be a link with auxin especially considering that this hormone also affects xylem differentiation [173]. It has been observed that plasma treatment modified the diameters of root and stems as well as the differentiation of tissues such as xylem and phloem [51,52,58,174]. These changes in root morphology may then enhance nutrient exchange [68] which was also proposed by Zahoranová et al [97].…”
Section: Hormonesmentioning
confidence: 79%
“…The role of high-energy photons in plasma-seed treatments has been controversial since UV has had a negligible effect so far but the effects of UV on seeds and plants could theoretically contribute to the wettability or growth enhancement effects indirectly; for example, by producing radicals or reactive oxygen species (ROS) such as ozone [60]. Gao et al [52] checked the effects of UV separately from plasma and observed that UV had only a minor contribution toward the seed wettability. Sarinont et al [102] also reported that there was no effect from UV when they saw the lack of growth enhancement effect after they blocked UV with a quartz plate.…”
Section: Ultraviolet Light (Uv)mentioning
confidence: 99%
See 2 more Smart Citations
“…Surface morphology information can be obtained using scanning electron microscopy (SEM). Seed coat erosion in plasma-treated seeds is the most common effect observed by SEM (Stolárik et al, 2015;Junior et al, 2016;Ambrico et al, 2017;da Silva et al, 2017;Guo et al, 2017;Li et al, 2017;Wang et al, 2017;Gao et al, 2019) but this does not necessarily occur in every instance. For example, Mildaziene et al (2016) noticed etching only on the seed surface facing the plasma, while other authors did not remark any (Sera et al, 2010;Bormashenko et al, 2012;Kitazaki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%